Religion and mental health: an Eastern Mediterranean region perspective - Ghuloum, Suhaila; Al-Thani, Haya A. Q. F.; Al-Amin, Hassen (Frontiers in Psychology, 2024)
In the last decade, spirituality gained increasing recognition, with an individualized approach to the significance of symptoms and the purpose of treatment. Many psychiatrists started adopting the term 'biopsychosocial-spiritual' management. Modern psychological therapies have drawn from the principles of ancient Eastern traditions. However, the spiritual beliefs within Islam and their impact on mental well-being have yet to be studied sufficiently. The Eastern Mediterranean region is largely Muslim and shares similar cultural beliefs. This paper explores some of these beliefs and their impact on perceptions of mental health and helpseeking behavior. The paper will focus primarily on the religious ideologies, the concepts of punishment and reward from Allah (God) in the context of the high stigma associated with mental illness in the region, and the knowledge, attitudes, and perceptions towards people with mental illness. We will explore cultural beliefs in possession, evil eye, and black magic and how they influence treatment adherence. Traditional and faith healers remain very popular in this part of the world and are often the first line of treatment for people presenting with mental illness. Suicide and self-harming are particularly sensitive areas due to their religious implications in life and death, as well as the afterlife. Despite the global interest in the Eastern Mediterranean region, there still is a shortage of research on the intercultural aspects of this region, especially regarding mental health assessments. In this regard, we will explore some published literature from Qatar and draw comparisons with regional findings.